1984
DOI: 10.1111/j.1471-4159.1984.tb05393.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Metabolism in the Brain of Young Rats Intoxicated with Organic and Inorganic Lead

Abstract: The activities of lipoyl dehydrogenase, aspartate transaminase, and alanine transaminase, and levels of lactate were estimated in cerebral cortex, cerebellum, and brainstem of rats intoxicated acutely with tetraethyl lead and chronically with lead acetate. A significant inhibition of lipoyl dehydrogenase was observed in both groups of animals, whereas transaminase activities were increased in inorganic lead toxicity. Oxidative decarboxylation and anaplerosis of pyruvate was assessed in brain slices using [1-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Lead induced a significant genotoxic effect indicated by increased rate of micronucleus and chromosomal aberrations. Many studies have demonstrated similar results, that lead changes the liver functions inducing liver fattening and increased AST, ALT, ALP, lactate dehydrogenase enzymes and decreased albumin/globulin ratio and changed serum lipid values (Mikhail et al 1980;Regunathan & Sundaresan 1984;Othman & El Missiry 1998;Todorovic & Vujanovic 2002;Sivaprasad et al 2003).…”
Section: Discussionmentioning
confidence: 83%
“…Lead induced a significant genotoxic effect indicated by increased rate of micronucleus and chromosomal aberrations. Many studies have demonstrated similar results, that lead changes the liver functions inducing liver fattening and increased AST, ALT, ALP, lactate dehydrogenase enzymes and decreased albumin/globulin ratio and changed serum lipid values (Mikhail et al 1980;Regunathan & Sundaresan 1984;Othman & El Missiry 1998;Todorovic & Vujanovic 2002;Sivaprasad et al 2003).…”
Section: Discussionmentioning
confidence: 83%
“…This is supported by the present study where lead exposure at the present dose and duration causes suppressed the activity of PDH in the liver. LA induced inhibition of PDH activity was also observed in a rat model [36]. Inhibition of PDH activity may be due to the selective affinity of divalent cation as like lead towards the sulphydryl groups of the enzyme [23].…”
Section: Discussionmentioning
confidence: 72%
“…TEL causes irreversible neuronal death in some areas of the brain (see Seawright et al, 1984), an effect thought to be mediated by an excitotoxic mechanism (see Cremer, 1984). It has been found to be an inhibitor of pyruvate metabolism in the cortex of the rat brain both in vivo and in vitro (Regunathan and Sundaresan, 1984). TEL has been reported to prevent the y-aminobutyric acid reuptake mechanism of synaptosomes independently of energy levels and of external C1- (Seidman and Verity, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In isolated mitochondria, TEL and TET have been shown to prevent pyruvate transport independently of the energy state of mitochondria (Skilleter, 1975). On the other hand, TEL has been shown to be an inhibitor of pyruvate decarboxylation in the rat cortex (Regunathan and Sundaresan, 1984). TEL stimulates synaptosomal glycolysis more extensively than respiration, suggesting that glycolytic substrates are available for mitochondria (Kauppinen and Komulainen, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%